2004
DOI: 10.1097/01.alc.0000141821.06062.20
|View full text |Cite
|
Sign up to set email alerts
|

Association of ALDH1 Promoter Polymorphisms With Alcohol‐Related Phenotypes in Southwest California Indians

Abstract: Results from this study suggest that ALDH1A1*2 may be associated with protection from the development of alcohol and other substance use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
6
42
0
1
Order By: Relevance
“…67 Moreover, a recent study has shown association between ALDH1 promoter polymorphisms and alcohol-related phenotypes in southwest California Indians. 120 Moreover, there is evidence of decreases in ALDH1 levels in post-mortem brains of persons with , and body weight in adult, male P rats (n ¼ 6-8/group). Lisinopril only affected the EtOH intake (top panel).…”
Section: Alcohol Metabolismmentioning
confidence: 98%
“…67 Moreover, a recent study has shown association between ALDH1 promoter polymorphisms and alcohol-related phenotypes in southwest California Indians. 120 Moreover, there is evidence of decreases in ALDH1 levels in post-mortem brains of persons with , and body weight in adult, male P rats (n ¼ 6-8/group). Lisinopril only affected the EtOH intake (top panel).…”
Section: Alcohol Metabolismmentioning
confidence: 98%
“…Other than the ALDH2 Ã 2 allele, the genetic influence of ALDHs on the risk for alcohol dependence appears, if present, to be modest. Protective roles against alcohol dependence have been suggested for the ALDH1A1 Ã 2 allele in Southwest California Indians [108] and for the ALDH1A1 Ã 3 allele in African Americans [106].…”
Section: Aldehyde Dehydrogenasementioning
confidence: 99%
“…The impact of functional variation in ADH1B and ALDH2 genes on alcohol metabolism have been fairly well characterized; however, there are large interindividual differences in alcohol elimination rates that still remain unexplained. Of potential signi fi cance in this regard may be polymorphisms in ADH4 [ 90,91 ] , ADH7 [ 39,69 ] , and ALDH1A1 [ 92,93 ] as well as the promoter regions of ALDH2 [ 94 ] . Further studies are needed to evaluate the in fl uence of these polymorphisms on the activity of ADH and ALDH and on alcohol levels and elimination rates in individuals, as well as on the physiological response to alcohol consumption and alcoholism.…”
Section: Discussionmentioning
confidence: 99%